A HISTOCHEMICAL STUDY ON THE CIRCULATING LIPOPHAGES IN CHOLESTEROL FED GUINEA PIGS - H. Al-Shebeb, T.; S. Al-Nassir, H. (The Iraqi Journal of Veterinary Medicine, 1990)
The postulation that circulating lipophages in cholesterol-fed guinea pigs may originate from lipidladen splenic macrophages was tested. The experimental animals were allocated in two groups: high-cholesterol (HC) and control (C) groups. Wright-Giemsa, Oil-red 0, non specific estrase and Perl’s prussian blue stains were. performed on peripheral blood films on both day-30 and 60 of the experiment. Vacuolated leukocytes were demonstrated by day 60 in the HC group and proven to be lipid-laden monocytes. No hemosiderin residue was detected in the circulating lipophages. Our data suggest that lipophages are unlikely to be splenic origin.